The Effect of Service Quality on Trust and Its Implications for Patient Loyalty - Zahara, Rita (Dinasti Publisher, 2024)
The purpose of this study was to determine and analyze: (1) Patient service quality at Clinic X, (2) Patient trust at Clinic X, (3) Patient loyalty at Clinic X, (4) Service quality on patient trust at Clinic X, (5) How much influence does service quality have on patient loyalty at Clinic X, (6) How much influence does patient trust have on patient loyalty at Clinic X.The research method used in this research is quantitative method. The research population is BPJS patients who come to Clinic X in 2022, which is 8,572 people. Based on the Slovin formula, a sample of 100 people was taken. The results showed that service quality has a significant influence on the level of patient trust, service quality also has a significant influence on patient loyalty, besides that patient trust has a significant influence on patient loyalty. However, testing the mediating variable shows that patient trust does not mediate the effect of service quality on patient loyalty. Service quality, trust, and patient loyalty need to be improved further, for this reason it is recommended for Clinic X to design strategies that promote active patient involvement in their care, such as regular health monitoring programs, responsive customer service, and incentives for loyal patients and conduct socialization in advance when a new product will be launched.